Consulting Foundations: Client Management and Relationships. - Lotardo, Elizabeth; Earle McLeod, Lisa (linkedin.com, 2018)
Client relationships are the foundation of your consulting business. Learn tips for communicating effectively, developing rapport, and building long-lasting business connections.